Culturally Modified Trees, Indian Reserves and the Crown's Fiduciary Obligations - McNeil, Kent (Osgoode Digital Commons, 2003)
The Supreme Court of Canada delivered three decisions in 2002 involving the Aboriginal peoples of Canada. None of these decisions dealt directly with Aboriginal or treaty rights. They were concerned instead with provincial authority in relation to Aboriginal cultural property, creation of and entitlement to Indian reserves, and the Crown's fiduciary obligations. I will begin by providing a brief description of the cases. Kitkatla Band v. British Columbia (Minister of Small Business, Tourism and Culture) involved a constitutional challenge to the applicability of the British Columbia Heritage Conservation Act to cultural objects - specifically, culturally modified trees - that were claimed by the Kitkatla First Nation to be part of their heritage. The Kitkatla argued that the provincial statute could not authorize the alteration or destruction of these trees, as protection of them fell within exclusive federal jurisdiction over "Indians, and Lands reserved for the Indians." The Supreme Court disagreed, for reasons discussed in this paper. The other two cases involved reserve lands. Ross River Dena Council Band v. Canada' arose from a disagreement between the Ross River First Nation and the Canadian government over whether lands in the Yukon set aside for the use of that First Nation constituted a reserve within the meaning of the Indian Act. Wewaykum Indian Band v. Canada involved a dispute between two Indian bands belonging to the same First Nation over their respective entitlements to two reserves on Vancouver Island. These cases provide considerable clarification of the law respecting the creation of Indian reserves and the Crown's fiduciary obligations in that regard.